Online Learning Activities During the Covid-19 Pandemic - Markuna, Markuna (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The COVID-19 pandemic impacts psychological conditions and impacts the education system in Indonesia. This study aims to analyze online learning activities during the Covid-19 pandemic in the Tarbiyah Department. This study uses a descriptive method with a qualitative approach with informants consisting of lecturers and students. The type of data collected is secondary data in the form of research results from various articles, library sources, and documents and elaboration sentences from the answers of research subjects conducted by interview. The research instrument consisted of an interview guide. The technique used to analyze the data is descriptive qualitative, and quantitative analysis. The research results are learned during the Covid-19 pandemic using an online model with V-class, Zoom, WhatsApp, Telegram, Google Class, Youtube, Facebook, and Messenger. The implementation of online learning runs smoothly, although it is not ideal. Student learning outcomes vary, ranging from unsatisfactory moderate to good. Constraints students and lecturers face in online learning include the availability of internet quotas, unstable networks, and supporting tools such as gadgets and laptops. Online learning is considered adequate if applied during the COVID-19 pandemic, but the required model is more attractive if used in the long term.